1996
DOI: 10.3109/10428199609052417
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplasia and acute myeloid leukemia occurring after autologous bone marrow transplantation for lymphoma

Abstract: Secondary hematopoietic disease manifesting as acute myeloid leukemia, myelodysplastic syndrome or clonal karyotypic abnormalities, has been recently recognized as a relatively frequent and potentially serious complication of autologous bone marrow transplantation for both Hodgkin's disease and non-Hodgkin's lymphoma. The available evidence suggests the disease results primarily from repeated exposure of the host stem cells to therapeutic agents before the time of transplant, but a conspiratory role for the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…[40][41][42][43][44][45][46] It is suggested that prolonged dysfunction of the haematopoietic system leads to the emergence of these secondary diseases, 43,47 typically occurring between 2 and 10 years after chemotherapy with the peak incidence after 5 years. Incidences up to 19.8% at 10 years have been reported following transplantation for non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44][45][46] It is suggested that prolonged dysfunction of the haematopoietic system leads to the emergence of these secondary diseases, 43,47 typically occurring between 2 and 10 years after chemotherapy with the peak incidence after 5 years. Incidences up to 19.8% at 10 years have been reported following transplantation for non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…MDS may occur as a consequence of marrow injury caused by chemotherapeutic agents or radiation used to treat prior benign or malignant conditions. [3][4][5][6][7] More commonly, MDS may occur as a primary disorder, in which no ascertainable cause for the disease can be identified. Even in the absence of leukemic evolution, most patients with MDS succumb to infection or transfusion-related complications, such as platelet alloimmunization or iron overload.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] From our institution we have previously (ASCT) and was followed for relapse and development of leu- followed by ASCT for malignant lymphomas, in most cases During the period January 1991 to July 1995 a total of 27 t-MDS and t-AML rather than the BEAM and ASCT regimen, which however may accelerate the evolution of the disease.patients with Hodgkin's disease and 49 patients with nonKeywords: therapy-related leukemia; secondary leukemia; maligHodgkin lymphomas received high-dose chemotherapy with nant lymphomas; BEAM chemotherapy; autologous stem cell trans-BEAM followed by ASCT in our department. BEAM consisted plantation of carmustine 300 mg/m 2 day 1 followed by etoposide 100 mg/m 2 twice a day plus cytosine-arabinoside 400 mg/m 2 daily for 4 days followed by melphalan 140 mg/m 2 on day 6.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9] From our institution we have previously (ASCT) and was followed for relapse and development of leu- followed by ASCT for malignant lymphomas, in most cases During the period January 1991 to July 1995 a total of 27 t-MDS and t-AML rather than the BEAM and ASCT regimen, which however may accelerate the evolution of the disease.…”
mentioning
confidence: 99%